Determinación del grado de compactación del suelo en área pastoril en la ganadería de la Universidad Técnica de Babahoyo. - Guanoluisa Suarez, Aracely Alexandra (2025)
The pressures exerted by animals through grazing is an aggravating factor since soil compaction is formed, causing plants to lose their normal state of growth both externally and internally, preventing the expansion of roots, water flow and porosity are also some of the causes that come from compaction. Compaction reduces soil yield because of the deterioration of physical, chemical and biological properties. Soil susceptibility varies according to texture, with clay soils being more vulnerable than sandy soils. In the present work, it is desired to demonstrate statistically if the soil of the FACIAG cattle ranch has an adequate degree of compaction so that the pastures are adequate to guarantee good quality pastures to be consumed by the cattle in a successful way. In this work we want to demonstrate statistically if the soil of the FACIAG livestock farm has an appropriate degree of compaction so that the pastures are adequate to ensure good quality pastures to be consumed by livestock successfully. A completely randomized design method (CRD) was used, in the field work was carried out by collecting samples of the different depths once this was finished we proceeded to take them to the laboratory to process the samples and thus we could obtain the results with a real density of the different depths with a coefficient of variation of 4.68% resulting that the best treatment was obtained at a depth of 10 cm with a 2.7 g/cm³; a bulk density of the different depths with a coefficient of variation of 4.29% with a depth of 10 cm was obtained 1.23 g/cm³ ; porosity with a coefficient of variation of 4.84% showed that the most suitable was the 30 cm with 55.19%; gravimetric moisture with a coefficient of variation of 8.23% it was determined that the sample at 20 cm was more suitable with 7.75%; Volumetric moisture with a coefficient of variation of 9.93% highlighted that the best treatment was 20 cm with 20.57% and the percentage of compaction of the different depths with a coefficient of variation of 5.86% resulted in the treatment at 10 cm being the most suitable with a compaction of 46%.